Studi Perbandingan Analisa Pemilihan Rute Jalan Tol Krian – Legundi – Bunder – Manyar Berdasarkan Karakteristik Jalan dan Pengguna Jalan - Yanida Agustina; Hera Widyastuti (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2023)
KLBM Toll Road is one of the Non-Trans-Java Toll Road projects connecting Sidoarjo Regency and Gresik Regency. The demand of toll roads needs to be considered in toll road planning. Traffic assignment analysis is carried out by calculating the benefits given due to the characteristics of a road. While the characteristics of road users are not accommodated in the road infrastructure planning and result in